2020
DOI: 10.1186/s12934-020-01349-6
|View full text |Cite
|
Sign up to set email alerts
|

Repeated fed-batch strategy and metabolomic analysis to achieve high docosahexaenoic acid productivity in Crypthecodinium cohnii

Abstract: Background: Docosahexaenoic acid (DHA) is essential for human diet. However, high production cost of DHA using C. cohnii makes it currently less competitive commercially, which is mainly caused by low DHA productivity. In recent years, repeated fed-batch strategies have been evaluated for increasing the production of many fermentation products. The reduction in terms of stability of culture system was one of the major challenges for repeated fed-batch fermentation. However, the possible mechanisms responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…There are some similar studies on oleagineous model systems including thraustochytrids [29][30][31][32]44,45] but none covering with quantitative methods the whole central carbon metabolism, redox-cofactors and lipid composition as completely as presented here. Those studies have mostly applied untargeted LC-MS and GC-MS profiling, few internal standards and usually only normalized to the total peak area.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are some similar studies on oleagineous model systems including thraustochytrids [29][30][31][32]44,45] but none covering with quantitative methods the whole central carbon metabolism, redox-cofactors and lipid composition as completely as presented here. Those studies have mostly applied untargeted LC-MS and GC-MS profiling, few internal standards and usually only normalized to the total peak area.…”
Section: Methodsmentioning
confidence: 99%
“…Yang and coworkers studied Schizochytrium strains with different DHA content and reported downregulated glycolytic and upregulated TCA pools in the high DHA strain [31]. Liu and coworkers applied GC-MS and LC-MS metabolite profiling to maintain high DHA productivity during repeated fed-batch cultivation of Crypthecodinium [32]. All these studies provide interesting information on the relative cellular adjustments to changes in cultivation conditions and growth stages which can be used to further improve yields and productivities of the DHA-bioprocess.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All cultivations were carried out with the strain E. coli BL21(DE3), transformed with a pET30a + plasmid carrying the gene for the cytoplasmic protein (CP) and periplasmic Crypthecodinium cohnii docosahexaenoic acid 4 cycles, 80% medium replacement Liu et al, 2020 Aspergillus terreus Lovastatin 3 cycles, 37% yield in crease Novak et al, 1997;Kumar et al, 2000 Gluconobacter oxydans Dihydroxyacetone 4 cycles, repeated fed-batch process using two spatially separated vessels Bauer et al, 2005 Kluyveromyces marxianus Ethanol 5 cycles, product yield constant Ozmihci and Kargi, 2007 Kitasatospora ε-Poly-L-lysine 5 cycles Zhang et al, 2010 Yarrowia lipolytica Citric acid 10 cycles, productivity decrease over cultivation time Moeller et al, 2011 Pichia pastoris human serum albumin (rHSA) 4 cycles, 47% yield increase Ohya et al, 2005 Pichia pastoris Malaria vaccine candidates stable productivity for 2-8 cycles, methanol induction Martens et al, 2011;Fricke et al, 2013 Escherichia coli Pyruvate 5 cycles, q p increased fivefold Zelić et al, 2004 protein (PP), respectively. The cytoplasmic protein contained no disulfide bonds, had a isoelectric point (PI) of 5.62 and a protein size of 26.9 kDa.…”
Section: Strainsmentioning
confidence: 99%
“…In recent years, significant efforts have been made to improve DHA productivity in C. cohnii using approaches such as optimizing fermentation conditions (Liu et al, 2018), employing different carbon sources (De Swaaf et al, 2003a,b), and enhancing strain improvement using the acetyl-CoA carboxylase inhibitor sethoxydim (Liu et al, 2017). However, certain bottlenecks remain, such as low tolerance to the inhibitory fermentation supernatant at the late stage of fermentation, which significantly limits further improvements of DHA productivity (Liu et al, 2020). It has been previously reported that the fermentation supernatant, in which the accumulation of unspent medium components or metabolites exported by C. cohnii at the late stage of fermentation occurs, could inhibit the growth and DHA synthesis in C. cohnii (Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%